Green Solution For Solid Waste Management - Shrivastava, Akrati; Singh, Jobanpreet; Priya, Smriti; Adhikary, Aritri; Brindha, S.; Ravichandran, S. (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 10 No 3&4 (2023): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2023)
Solid waste is the discarded solid materials produced from domestic, residential, commercial or industrial activities. On the basis of types of material such plastic, paper, metal organic waste, glass, toxic, industrial waste, domestic waste etc. Over population, industrialization, urbanization are mainly responsible for increasing rate of solid wastes. About 7.8 million tonnes of wastes have been produced worldwide and out of which 11-15% of which have been recycled. The solid waste Figure 1 management includes the generation of waste, storage, collection, transportation, processing and disposal. Improper solid waste management degrades people health, environmental pollution, depletion of natural resources, climate change which greatly impacts the quality of life on this earth. In this article, the solid waste types and the methods of solid waste disposal were discussed in detail.